Analyse Sprachlicher Fehler in der Fremdsprachlichen Kommunikation von Pflegefachkräften mit Patient:innen - Sarah Löwenkamp (Vestnik za Tuje Jezike)
The shortage of skilled workers is a growing and prevalent challenge for the labour market in Germany and the EU as a whole. One strategy to counter the shortage of skilled labour is to recruit qualified professionals from abroad. This involves the immigration of skilled workers with specific needs in terms of teaching and learning German as a Foreign Language/German as a Second Language, which need to be met in the best possible way. This article will therefore use an analysis of linguistic errors in a written task to determine the needs of foreign nursing staff with regard to learning German. This is done by aiming to identify any potential key areas in which errors may occur. The task places the participants in an authentic scenario from their everyday working life. The error analysis is also used to classify the extent to which these errors would limit the success of communication with their patients. This professional group was selected based on various relevant criteria: First, nursing professions belong to the group of professions with the greatest shortage on the labour market, and proof of German language skills is a bureaucratic requirement. In addition to the related technicalities, proficiency in German can also be considered essential for successfully navigating everyday working life. The group of participants is heterogeneous in terms of first language and German level, which reflects a common composition of these learning groups. Based on this heterogeneity and the fact that there is still potential for optimization despite existing teaching and learning materials specifically designed for the target group, the article proposes translanguaging as a new didactic approach for successfully mastering professional situations in a foreign language environment, both linguistically and professionally. Translanguaging can thus be described as the lens through which the results of the task at hand are viewed.